Exploring Mobile Legends Bang Bang (MLBB) as a Tool for Enhancing English Vocabulary Among High School Learners - Tia Rahmatika (Journey: Journal of English Language and Pedagogy, 2025)
This qualitative study explores the impact of the mobile game Mobile Legends Bang Bang (MLBB) in enhancing English vocabulary among high school learners at SMK Darussalam Samarinda. The participants were 15 third-year vocational students selected through purposive sampling based on the following criteria: (1) active MLBB players for at least six months, (2) users of the English-language game interface, and (3) voluntary participation. The research examined participants’ experiences with vocabulary acquisition through gameplay, focusing on exposure to new words, contextual learning, social interaction, and academic relevance. Using a thematic analysis based on Miles and Huberman’s methodology, the researcher found that participants’ impressions of their vocabulary growth were mixed, but overall favourable. Findings indicate that MLBB serves as an engaging and effective tool for informal vocabulary growth, particularly through frequent encounters with new terms and interactive communication features. While learners often applied gaming vocabulary in daily conversation, transfer to formal academic contexts was less consistent. This study adds to our knowledge of mobile-assisted language learning by illuminating the pros and cons of using digital games like MLBB as part of language acquisition frameworks in the classroom.